Follow-up to the graduates, entrepreneurship and labor insertion of the graduates from the Technical University of Manabí’s Basic Education career - Idelisa Castro Bermúdez, Lázaro Clodoaldo Enríquez Caro, José Rafael ProenzaPupo, Oscar Egberto Mera Chinga, Luis Alfredo Vera García, Gladys Consuelo Acosta Guerra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The follow-up to the graduates, as an activity inherent to higher education institutions, allows to achieve a vision of the training accomplished by the professionals and their labor insertion. The objective of this work was to explore thegraduates’ level of intentions to undertake in the educational field of the of the basic general education career of the Technical University of Manabí. A mixed cross-sectional study involving 62 students was conducted. An “adhoc”instrument based on the survey (Ortiz 2016), and the indicators of the GEM project was used. The results showed a low level of entrepreneurship and a high percent of students who do not believe they can undertake in this field. The unfavorable labor situation evidenced (82% do not work in the field of education) indicates the need to find alternatives for these graduates, in this scenario, training on entrepreneurship can be an effective option.